2010
DOI: 10.1007/s13239-010-0014-6
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of a Pulsatile Conditioning System for Dynamic Endothelialization of Polyphenol-Stabilized Tissue Engineered Heart Valves

Abstract: Heart valve tissue engineering requires biocompatible and hemocompatible scaffolds that undergo remodeling and repopulation, but that also withstand harsh mechanical forces immediately following implantation. We hypothesized that reversibly stabilized acellular porcine valves, seeded with endothelial cells and conditioned in pulsatile bioreactors would pave the way for next generations of tissue engineered heart valves (TEHVs). A novel valve conditioning system was first designed, manufactured and tested to ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 32 publications
3
51
2
1
Order By: Relevance
“…in cardiovascular tissue engineering, Jockenhoevel et al 34 and other research groups showed that flow-depending mechanical stress induces ECM formation. 35 in line with these results, the establishment of an ECM and the habituation of the cells were observed during the 5-day conditioning periods, demonstrated by positive staining against collagen iV and fibronectin. An increased ECM growth on scaffolds' inner/flow surface proved the flow dependence.…”
Section: Discussionsupporting
confidence: 83%
“…in cardiovascular tissue engineering, Jockenhoevel et al 34 and other research groups showed that flow-depending mechanical stress induces ECM formation. 35 in line with these results, the establishment of an ECM and the habituation of the cells were observed during the 5-day conditioning periods, demonstrated by positive staining against collagen iV and fibronectin. An increased ECM growth on scaffolds' inner/flow surface proved the flow dependence.…”
Section: Discussionsupporting
confidence: 83%
“…During harvesting of the aortic roots, we preserved about 2 cm of aorta above the sinus of Valsalva and 4 to 5 cm of endocardial tissue (thinned to 2–3 mm) and the anterior mitral leaflet. The coronary arteries were ligated using 2.0 TiCron suture and valves were immersion-decellularized with detergents and enzymes and sterilized according to published protocols [17]. To stabilize the valve ECM, the acellular roots were treated with 0.1% PGG, a collagen binding polyphenol [17].…”
Section: Methodsmentioning
confidence: 99%
“…Valve-derived scaffolds are preferred because of easy accessibility, outstanding hemodynamic properties and the preservation of biological "niches" after decellularization (10)(11)(12). We also treat acellular scaffolds with penta-galloyl glucose (PGG) for tissue stabilization, to prevent premature scaffold degradation and to reduce calcification (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%